Sistem Informasi MSDM Menggunakan Microsoft Access dan OneDrive pada Politeknik LP3I Kampus Depok - Sutan Mohammad Arif; Hendro Purwoko (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
Microsoft Access is a reliable database application and part of Microsoft Office application installation so that easy to be used in shorting the human resources of Politeknik LP3I Jakarta Kampus Depok. Currently, Management Information System of Human Resource on this campus, having an online system. However, the data information is less complete so that researcher try to make a cheap system by using "One Drive" as Cloud Computing service in order to be able to accessed by other users at the same time. Rapid Application Development method is used by the researcher in making the system to minimize the developing time. Research study shown that Microsoft Access used with the Cloud Computing One Drive service is proven easier and faster in shorting the employee at Politeknik LP3I Jakarta Kampus Depok. This application should be maintained and backed up regularly to preserve the data from damage